Pemberdayaan Pemuda Masjid di Desa Pelawad, Serang melalui Pelatihan Manajemen Keuangan (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2021)
Pelawad Village is one of the villages in the Ciruas sub-district, Serang Regency, where the majority of the population is Muslim. Pelawad Village has eight mosques. In the management of mosque finances, based on preliminary information received from the BKPM (Mosque Youth Communication Board) it has not been carried out properly. Almost all mosques do not yet have a good bookkeeping system. This activity aims to provide simple financial bookkeeping training with the theme Financial Management Training for Empowerment of Mosque Youth. The method used in this community service activity is an action study through a training approach for youth and adolescents in the Pelawad-Ciruas village environment. To make this happen, BKPM has collaborated with several Bina Bangsa University lecturers. The partnership cooperation between BKPM and Abdimas team at Bina Bangsa University is carried out with the following agreements: BKPM is responsible for providing training facilities and infrastructure as well as coordinating training participants. The community service team served as resource persons and provided training materials. This activity has an outcome that must be achieved, namely increasing the ability of mosque-based financial management. The activity was carried out by after isha considering that the participants were mosque administrators and BKPM members who were caretakers of the mosque, and lasted for 3 days while still observing strict health protocols.